2022
DOI: 10.1039/d2em00097k
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, mobile, and toxic plastic additives in Canada: properties and prioritization

Abstract: The hazards of many plastic additives on human and environmental health are well documented. However, little emphasis has been put on plastic additives that are persistent, mobile, and toxic (PMT)...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…This is also a potential source of uncertainty. However, despite the existence of various wastewater treatment processes, the literature indicated that melamine was hardly biodegraded in STP and was mainly removed by activated sludge adsorption. , Moreover, the latest SimpleTreat model screening showed that nearly 77.5% of melamine in STP entered the environment from effluent . Based on these reports, the EFs of melamine in STP selected in this study had good reliability, and the parameter sensitivity analysis also demonstrated that they had little impact on the estimated results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also a potential source of uncertainty. However, despite the existence of various wastewater treatment processes, the literature indicated that melamine was hardly biodegraded in STP and was mainly removed by activated sludge adsorption. , Moreover, the latest SimpleTreat model screening showed that nearly 77.5% of melamine in STP entered the environment from effluent . Based on these reports, the EFs of melamine in STP selected in this study had good reliability, and the parameter sensitivity analysis also demonstrated that they had little impact on the estimated results.…”
Section: Resultsmentioning
confidence: 99%
“…25,67 Moreover, the latest SimpleTreat model screening showed that nearly 77.5% of melamine in STP entered the environment from effluent. 49 Based on these reports, the EFs of melamine in STP selected in this study had good reliability, and the parameter sensitivity analysis also demonstrated that they had little impact on the estimated results. We acknowledge that this study does not contain a complete picture of melamine emissions to the environment but rather quantifies emissions that were associated with the direct production and use of melamine.…”
Section: Priority Analysis Of the Melamine Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies ranked PMT/vPvM substances based on their emission potential to the environment 43 or their mobility through waste water treatments. 44 Half of the PMT/vPvM substances identied in the CosIng database are listed on these prioritisation lists (Table SI2.1 †). This emphasises that, whilst we selected the most frequently occurring PMT/vPvM substances in cosmetics based on data from Kemiluppen and Cosmethics, many other relevant substances, uses and consequent emissions need to be addressed in future studies.…”
Section: Pmt/vpvm Substances In Cosmeticsmentioning
confidence: 99%
“…12 Understanding the environmental degradation of plastics is essential to understanding the risks posed by plastic litter, and how this varies depending on the polymer in question. Environmental degradation can release hazardous chemicals added to plastics, such as ame-retardants, stabilizers or plasticizers, 13,14 and enhance the sorption of hazardous pollutants such as polycyclic aromatic hydrocarbons (PAHs), e.g., Udenby et al 15 Several weathering processes affect environmental plastics: biodegradation, photodegradation, thermo-oxidative degradation, thermal degradation, hydrolysis 16 and mechanical degradation (abrasion). Polymer degradation can be dened as depolymerisation, overall mass loss, or complete mineralization to CO 2 and H 2 O and involves both physical (related to the bulk structure) and chemical (molecular level) changes.…”
Section: Introductionmentioning
confidence: 99%